INCREASED DENTAL IMPLANT OSTEOINTEGRATION IN MENOPAUSAL OSTEOPOROSIS IN WOMEN - Achilova Nodira Ganievna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Introduction Osteoporosis is a systemic skeletal disease that is accompanied by a decrease in bone density and changes in bone microarchitecture, leading to increased fragility and a  high  risk  of  fractures[1][2].  According  to  WHO  data,  approximately  every  third woman and every fifth man over 50 suffers from osteoporosis[1][3]. In Russia, the prevalence  of  osteoporosis  among  women  after  50  years  is  ~33.8%,  among  men  - ~26.9%[1]; the number of diagnosed patients is close to 14 million people[4][3]. In postmenopause  in  women,  calcium  leaching  from  bones  accelerates,  which  is especially relevant for dental implantation: insufficient bone volume of the alveolar ridge  can  limit  the  possibility  of  full-fledged  osteointegrative  implantation.  On  the other hand, dental implants are successfully implanted in patients with osteoporosis. Recent publications indicate high survival rates of implants (>90-95%) even in women with  osteoporosis[6][7].  Due  to  the  increasing  number  of  elderly  patients  and  the prevalence  of  osteoporosis,  the  task  of  ensuring  reliable  osseointegration  during menopause in women is becoming increasingly important both in maxillofacial surgery and in dental practice. The purpose of this work is to summarize modern data on the impact  of  osteoporosis  (including  drug-induced  osteoporosis  when  taking bisphosphonates)  on  the  osteointegration  of  dental  implants  in  women  during  the climacteric  period  and  to  examine  modern  approaches  (PRGF,  osteoplasty,  3D-planning) to treating such patients.